Chemokine Receptor-5Δ32 Mutation is No Risk Factor for Ischemic-Type Biliary Lesion in Liver Transplantation - Christoph Heidenhain; Gero Puhl; Christian Moench; Anja Lautem; Peter Neuhaus (Journal of Transplantation)
It has been shown that certain chemokine receptor polymorphisms may correspond to certain complications after organ transplantation. Ischemic-type biliary lesion (ITBL) encounters for major morbidity and mortality in liver transplant recipients. So far, the exact cause for ITBL remains unclear. Certain risk factors for the development of ITBL like donor age and cold ischemic time are well described. In a previous study, a 32-nucleotide deletion of the chemokine receptor-5Δ32 (CCR-5Δ32) was strongly associated with the incidence of ITBL in adult liver transplantation. This study re-evaluates the association of CCR-5Δ32 gene polymorphism and the incidence of ITBL. 169 patients were included into this retrospective analysis. 134 patients were homozygous for wild-type CCR-5, 33 patients heterozygous, and 2 patients were homozygous for CCR-5Δ32 mutation. There were no major differences in donor or recipients demographics. No association was found between CCR-5Δ32 mutation and the development of ITBL. We conclude that CCR-5Δ32 is no risk factor for the development of ITBL in our patient cohort.